EIB Impact Report 2020 Climate action, environmental sustainability and innovation for decarbonisation - European Investment Bank (European Investment Bank, 2021)
Investments supported by the European Investment Bank help achieve EU and international policy goals. The report specifically measures the effectiveness of our investments in three key areas: Additionality: the EIB's role is to step in where the market has failed to deliver. Specifically, the EIB examines how our support for a project strengthens it compared to what would have happened without our involvement. Impact: The EIB now measures how its investments contribute to the United Nations Sustainable Development Goals (SDGs). By doing so, the EIB is signalling its commitment to supporting the United Nations' Decade of Action to create peace and prosperity for people and the planet. Climate: The 2021 report focuses on barriers to investment in climate action, environmental sustainability and research and development and innovation for the decarbonisation of energy-intensive industries.